Resistance of the Lichen Buellia frigidato Simulated Space Conditions during the Preflight Tests for BIOMEX—Viability Assay and Morphological Stability - Meeßen, J.; Wuthenow, P.; Schille, P.; Rabbow, E.; de Vera, J.-P.P.; Ott, S. (Astrobiology, 2015)
Samples of the extremotolerant Antarctic endemite lichen Buellia frigida are currently exposed to low-Earth orbit– space and simulated Mars conditions at the Biology and Mars Experiment (BIOMEX), which is part of the ESA mission EXPOSE-R2 on the International Space Station and was launched on 23 July 2014. In preparation for the mission, several preflight tests (Experimental and Scientific Verification Tests, EVT and SVT) assessed the sample preparation and hardware integration procedures as well as the resistance of the candidate organism toward the abiotic stressors experienced under space and Mars conditions. Therefore, we quantified the post-exposure viability with a live/dead staining technique utilizing FUN-1 and confocal laser scanning microscopy (CLSM). In addition, we used scanning electron microscopy (SEM) to investigate putative patterns of morphological-anatomical damage that lichens may suffer under the extreme exposure conditions. The present results demonstrate that Buellia frigida is capable of surviving the conditions tested in EVT and SVT. The mycobiont showed lower average impairment of its viability than the photobiont (viability rates of >83% and >69%, respectively), and the lichen thallus suffered no significant damage in terms of thalline integrity and symbiotic contact. These results will become essential to substantiate and validate the results prospectively obtained from the returning space mission. Moreover, they will help assess the limits and limitations of terrestrial organisms under space and Mars conditions as well as characterize the adaptive traits that confer lichen extremotolerance.